Problemy opałowe Łodzi w latach I wojny światowej - Stawiszyńska, Aneta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The outbreak of the Great War disorganized the life of the citizens of Lodz, making a normal existence nearly impossible. One of the biggest problems was the lack of combustible materials. Due to irregular supplies of coal, the people of Lodz were cutting down forests and parks trees located around the city. Occasional transports of combustible materials were transferred to social institutions, such as schools or hospitals at first place. Even though the city authorities provided numerous forms of support, such as peat and coke supplies or timber distribution, the problem was not solved. People were stealing parts of wooden constructions, such as fences and destroyed houses on massive scale. Lack of coal made it impossible to work in many institutions, such as power stations and gasworks.